How to measure lineup fairness: concurrent and predictive validity of lineup-fairness measures - Lee, Jungwon (Psychology, crime & law, 2025)
The current study examined the concurrent and predictive validity of four families of lineup-fairness measures – mock-witness measures, perceptual ratings, face-similarity algorithms, and resultant assessments (assessments based on eyewitness participants’ responses) – with 40 mock crime/lineup sets. A correlation analysis demonstrated weak or non-significant correlations between the mock-witness measures and the algorithms, but the perceptual ratings correlated significantly with both the mock-witness measures and the algorithms. These findings may reflect different task characteristics – pairwise similarity ratings of two faces versus overall similarity ratings for multiple faces – and suggest how to use algorithms in future eyewitness research. The resultant assessments did not correlate with the other families, but a multilevel analysis showed that only the resultant assessments – which are based on actual eyewitness choices – predicted eyewitness performance reliably. Lineup fairness, as measured using actual eyewitnesses, differs from lineup fairness as measured using the three other approaches.